Asthma and Rhinitis Induced by Selective Immediate Reactions to Paracetamol and Non-steroidal Anti-inflammatory Drugs in Aspirin Tolerant Subjects - Pérez-Alzate, Diana; Blanca-López, Natalia; Doña, Inmaculada; Agúndez, José A.; García-Martín, Elena; Cornejo-García, José A.; Perkins, James R.; Blanca, Miguel; Canto, Gabriela (Frontiers in Pharmacology, 2016)
In subjects with non-steroidal anti-inflammatory drugs (NSAIDs)- exacerbated respiratory disease (NERD) symptoms are triggered by acetyl salicylic acid (ASA) and other strong COX-1 inhibitors, and in some cases by weak COX-1 or by selective COX-2 inhibitors. The mechanism involved is related to prostaglandin pathway inhibition and leukotriene release. Subjects who react to a single NSAID and tolerate others are considered selective responders, and often present urticaria and/or angioedema and anaphylaxis (SNIUAA). An immunological mechanism is implicated in these reactions. However, anecdotal evidence suggests that selective responders who present respiratory airway symptoms may also exist. Our objective was to determine if subjects might develop selective responses to NSAIDs/paracetamol that manifest as upper/lower airways respiratory symptoms. For this purpose, we studied patients reporting asthma and/or rhinitis induced by paracetamol or a single NSAID that tolerated ASA. An allergological evaluation plus controlled challenge with ASA was carried out. If ASA tolerance was found, we proceeded with an oral challenge with the culprit drug. The appearance of symptoms was monitored by a clinical questionnaire and by measuring FEV1 and/or nasal airways volume changes pre and post challenge. From a total of 21 initial cases, we confirmed the appearance of nasal and/or bronchial manifestations in ten, characterized by a significant decrease in FEV1% and/or a decrease in nasal volume cavity after drug administration. All cases tolerated ASA. This shows that ASA tolerant subjects with asthma and/or rhinitis induced by paracetamol or a single NSAID without skin/systemic manifestations exist. Whether these patients represent a new clinical phenotype to be included within the current classification of hypersensitivity reactions to NSAIDs requires further investigation.